Culture conditions influencing phytase production of Mitsuokella jalaludinii, a new bacterial species from the rumen of cattle - Lan, G.Q.; Abdullah, N.; Jalaludin, S.; Ho, Y.W. (Blackwell Publishing, 2002)
Aims: The effects of pH, temperature, phytate, glucose, phosphate and surfactants on the phytase production of Mitsuokella jalaludinii, a new bacterial species from the rumen of cattle, were evaluated. Method and Results: By using batch fermentation, it was found that phytase production of M. jalaludinii was induced by sodium phytate. Inclusion of glucose into rice bran-soybean milk (RB-SM) medium inhibited the phytase production. Supplementation of 0.05-0.5% of phosphate to RB-SM medium neither inhibited nor stimulated the phytase production. The optimum pH and temperature for the phytase production of M. jalaludinii were 7.02 and 39°C, respectively. Surfactants such as Tween-80 (0.5% and 1.0%) and Triton X-100 (1.0%) did not affect the phytase production. Conclusions, Significance and Impact of the Study: The study has provided important data on the culture conditions affecting phytase production of M. jalaludinii, which will facilitate future research on the optimization of fermentation processes for production of high phytase activity by M. jalaludinii.